Smart Communications, Intelligent Algorithms and Interactive Methods Proceedings of 4th International Conference on Wireless Communications and Applications (ICWCA 2020) - Jain, Lakhmi C.; Kountchev, Roumen; Hu, Bin.; Kountcheva, Roumiana; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book gathers selected papers presented at the 4th International Conference on Wireless Communications and Applications (ICWCA 2020), held at Hainan University, China. The first volume of the proceedings will focus on the newest methods and algorithms in smart wireless communications in the areas of multimedia communications over wireless; smart antenna and space-time signal processing; antenna, wireless propagation, and channel modeling; OFDM and multi-carrier techniques; localization and navigation techniques; software-defined networking (SDN) and network function virtualization (NFV); knowledge-defined networking (KDN) and the applications of artificial intelligence (AI) in future networks; future data-center networks; resource allocation and orchestration in future networks and many others.
Algorithm and Application of Artificial Intelligence in Wireless Sensor Network Coverage -- Design of Cooperative Driving System Based on VANET -- A Study of Intelligent Power Information Collection System Based on Distributed Architecture -- A Multi-User Communication Algorithm for UAV Bee Combat -- Review on Dec-POMDP Model for MARL Algorithms -- Research on AGV Correction Control Method Using QR Code Positioning -- Research on Multi Data Center Collaboration Technology for Multi Station Fusion -- A Novel Method for Online Control in Equipment Parameters of Blow Molding Process -- Research on the Optimum Ratio of Intelligent Rail Guided Vehicle and Computer Numerical Control -- An Apple Grading Method Based on Improved VGG16 Network.
Keywords: Telecommunication; Wireless communication systems; Mobile communication systems; Computational intelligence; Communications Engineering, Networks; Wireless and Mobile Communication; Computational Intelligence; Wireless communication systems -- Congresses